Discovery of Novel Leaf Rust Responsive microRNAs in Wheat and Prediction of Their Target Genes - Kumar, Dhananjay; Singh, Dharmendra; Kanodia, Pulkit; Prabhu, Kumble Vinod; Kumar, Manish; Mukhopadhyay, Kunal (Journal of Nucleic Acids, 2014)
MicroRNAs are endogenous small noncoding RNAs which play critical roles in gene regulation. Few wheat (Triticum aestivum L.) miRNA sequences are available in miRBase repertoire and knowledge of their biological functions related to biotic stress is limited. We identified 52 miRNAs, belonging to 19 families, from next-generation transcriptome sequence data based on homology search. One wheat specific novel miRNA was identified but could not be ascribed or assigned to any known miRNA family. Differentially expressed 22 miRNAs were found between susceptible and resistant wheat near-isogenic lines inoculated with leaf rust pathogen Puccinia triticina and compared with mock inoculated controls. Most miRNAs were more upregulated in susceptible NIL compared to resistant NIL. We identified 1306 potential target genes for these 52 miRNAs with vital roles in response to stimuli, signaling, and diverse metabolic and cellular processes. Gene ontology analysis showed 66, 20, and 35 target genes to be categorized into biological process, molecular function, and cellular component, respectively. A miRNA-mediated regulatory network revealed relationships among the components of the targetome. The present study provides insight into potential miRNAs with probable roles in leaf rust pathogenesis and their target genes in wheat which establish a foundation for future studies.